Self Care of the Elderly in Huayod District, Trang Province, Thailand - ดุลยเกียรต, ิจิรายุส (Journal of Health Science of Thailand, 2020)
The objectives of this descriptive study were to study and to compare self health care of the elderly on the variables of sex and occupations of the elderly. The research population were elderly of both sexes, living in the villages of Huayod District, Trang Province, Thailand. The sample size of 532 were stratified randomly drawn from the 7168 person in 133 villages. The instrument used for data collection was a set of questionnaire verified for content validity and reliability. Data were collected in April 2020. The returned questionnaire were 472 from 532 (88.72%). The obtained data were then statistically analysed by percentiles, mean and standard deviations. The t-test and one-way analysis of variance were applied to determine the significant differences between means by Schaffe, s test. The results of this study revealed that most of the samples were female (64.61%), with the age range from 65 to 69 years old (42.50%), had primary school education (86.82%) and were famers (61.65%). Most of them had received health education on self care from health care teams (76.80%). Self care were reported at a good level on nutrition, rest and sleep, exercise, narcotics drug and mental health. The comparison of self care between the males and females revealed there were no statistical differences at 0.05 level. Likewise, comparison of self care in elderly among different occupation showed no statistical differences at 0.05 level. As a result, it is highly recommended that self care in elderly should be encouraged and promoted by family, health care team and elderly groups continuously. Participation and group process have brought about many changes to members especially the experiences on self care of the elderly.